2013
DOI: 10.1111/odi.12197
|View full text |Cite
|
Sign up to set email alerts
|

Decreased submandibular adiponectin is involved in the progression of autoimmune sialoadenitis in non‐obese diabetic mice

Abstract: Adiponectin plays a protective role on submandibular cells. Decreased adiponectin might promote glandular destruction in autoimmune sialoadenitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
(68 reference statements)
3
9
0
Order By: Relevance
“…The impairment of epithelial cells directly results in the secretory dysfunction (Fox, ; Mitsias, Kapsogeorgou, & Moutsopoulos, ). Here, we found that apoptosis was increased in the submandibular glands of NOD mice, which is consistent with our previous study (Su et al, ). SHED treatment decreased apoptosis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The impairment of epithelial cells directly results in the secretory dysfunction (Fox, ; Mitsias, Kapsogeorgou, & Moutsopoulos, ). Here, we found that apoptosis was increased in the submandibular glands of NOD mice, which is consistent with our previous study (Su et al, ). SHED treatment decreased apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“…week-old mice. The SS-like phenotype in NOD mice was consistent with our previous study (Su et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As adiponectin promotes insulin sensitivity, a compensatory increase of expression of adiponectin may occur in the early stage of low insulin sensitivity of NOD mice. With development of autoimmune sialadenitis, the serum adiponectin level has been shown to decrease in NOD mice 38. Our results showed that, in response to ODN 1826 stimulation, placental adiponectin expression was downregulated in the NOD mouse but not in the WT mouse placenta.…”
Section: Discussionmentioning
confidence: 58%
“…Similarly in psoriasis, basal serum adiponectin levels were lower than healthy controls but increased with treatment [70,98,99]. Mice that develop sialoadenitis, a model for human Sjögren's syndrome, exhibit lower levels of glandular adiponectin, but this is likely related to localized production of adiponectin [100]. Clearly there is significant evidence that adiponectin impacts inflammatory autoimmunity, but unraveling the role of adiponectin in this context will require a better understanding of the potentially opposing functions it plays in inflammation, whether that is related to isoform differences or some other process.…”
Section: Adiponectinmentioning
confidence: 89%